Analysis of the Policy Background of Transport Related Use of Renewable Energy - Princz-Jakovics , Tibor (International Journal of Engineering and Management Sciences, 2019)
The EU energy policy prioritizes the following principles: sustainability, competitiveness and security of supply and addresses the reduction of greenhouse gas emissions as a priority. The related EU policy (including the White Paper on Transport) outlines these principles, identifies goals and opportunities for action. At company level methodological guidelines and standard procedures can be used to assess the carbon footprint of the organization, to generate efficiency goals and to prepare action plans. In the Hungarian policy framework, a comprehensive National Sustainable Development Framework Strategy defines the basic principles for the analysis of the sectorspecific or regional strategies. Sustainable Energy Action and Climate Plans (SECAPs) integrate energy and climate issues and include interventions and improvements for the better use of renewable energy sources in transport at municipal level. As a summary it can be stated that exploration of the policy background would needed to influence the use of renewable energy sources for transport and definition of the development goals can help economic organizations to transform their mobility patterns and reduce related carbon footprint.